2002
DOI: 10.1128/jb.184.1.29-42.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Phenotypic Analysis ofCaVRG4, Encoding an Essential Golgi Apparatus GDP-Mannose Transporter

Abstract: Cell surface mannan is implicated in almost every aspect of pathogenicity of Candida albicans. In Saccharomyces cerevisiae, the Vrg4 protein acts as a master regulator of mannan synthesis through its role in substrate provision. The substrate for mannosylation of proteins and lipids in the Golgi apparatus is GDP-mannose, whose lumenal transport is catalyzed by Vrg4p. This nucleotide sugar is synthesized in the cytoplasm by pathways that are highly conserved in all eukaryotes, but its lumenal transport (and hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 59 publications
(50 reference statements)
4
79
1
Order By: Relevance
“…The carbohydrate structure consists of the Man 8 GlcNAc 2 core that is extensively elaborated in the Golgi by the addition of the highly branched outer chain. Previous studies have demonstrated the overall importance of glycosylation to the cell wall structure and virulence (25)(26)(27). Loss of O-mannan has been shown to result in reduced adherence and the attenuation of virulence, suggesting that O-mannan may act as a ligand in the interaction with host surfaces (12, 14, 28 -31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The carbohydrate structure consists of the Man 8 GlcNAc 2 core that is extensively elaborated in the Golgi by the addition of the highly branched outer chain. Previous studies have demonstrated the overall importance of glycosylation to the cell wall structure and virulence (25)(26)(27). Loss of O-mannan has been shown to result in reduced adherence and the attenuation of virulence, suggesting that O-mannan may act as a ligand in the interaction with host surfaces (12, 14, 28 -31).…”
Section: Discussionmentioning
confidence: 99%
“…Null Mutant-Previously, the electrophoretic mobility of secreted acid phosphatase on native gels has been used as a maker of N-glycosylation status (13,25,27). However, no acid phosphatase activity was detected in zymograms of the Caoch1⌬ null mutant.…”
Section: Glycosylation Defects In the Caoch1⌬mentioning
confidence: 99%
See 1 more Smart Citation
“…GDP-mannose (GDP-Man) transporters have been studied in various organisms, such as the protozoan parasite Leishmania (20), S. cerevisiae (21), plants (22), and various fungi (23)(24)(25), including two Aspergilli (26,27). Mammalian cells do not possess any * This work was supported by the Deutsche Forschungsgemeinschaft.…”
mentioning
confidence: 99%
“…In fungi, GDP-Man transport is indispensable for modification of protein N-and O-glycans (28 -30), glycolipid biosynthesis (31), and GPI anchor substitution (32,33). It has been reported to be essential in Saccharomyces (21), Candida (23), and Aspergillus niger (26).…”
mentioning
confidence: 99%